Glycan-directed SARS-CoV-2 inhibition by leek extract and lectins with insights into the mode-of-action of Concanavalin A - Klevanski, Maja; Kim, Heeyoung; Heilemann, Mike; Kuner, Thomas; Bartenschlager, Ralf (Antiviral research, 2024)
Four years after its outbreak, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains a global challenge for human health. At its surface, SARS-CoV-2 features numerous extensively glycosylated spike proteins. This glycan coat supports virion docking and entry into host cells and at the same time renders the virus less susceptible to neutralizing antibodies. Given the high genetic plasticity of SARS-CoV-2 and the rapid emergence of immune escape variants, targeting the glycan shield by carbohydrate-binding agents emerges as a promising strategy. However, the potential of carbohydrate-targeting reagents as viral inhibitors remains underexplored. Here, we tested seven plant-derived carbohydrate-binding proteins, called lectins, and one crude plant extract for their antiviral activity against SARS-CoV-2 in two types of human lung cells: A549 cells ectopically expressing the ACE2 receptor and Calu-3 cells. We identified three lectins and an Allium porrum (leek) extract inhibiting SARS-CoV-2 infection in both cell systems with selectivity indices (SI) ranging between >2 and >299. Amongst these, the lectin Concanavalin A (Con A) exerted the most potent and broad activity against a panel of SARS-CoV-2 variants. We used multiplex super-resolution microscopy to address lectin interactions with SARS-CoV-2 and its host cells. Notably, we discovered that Con A not only binds to SARS-CoV-2 virions and their host cells, but also causes SARS-CoV-2 aggregation. Thus, Con A exerts a dual mode-of-action comprising both, antiviral and virucidal, mechanisms. These results establish Con A and other plant lectins as candidates for COVID-19 prevention and basis for further drug development.